Pengaruh Kualitas Kehidupan Kerja, Kepuasan Kerja Dan Komitmen Organisasional Terhadap Kinerja Karyawan (Studi Kasus pada Polisi Sektor Mojoroto Kediri) - Fitri Umayasari; Eddy Suwasono; Sumarji Sumarji (Otonomi, 2022)
This study aims to examine and analyze the effect of quality of work life, job satisfaction and organizational commitment on employee performance at Polsek Mojoroto. This study uses a quantitative approach. The population in this study were all employees of the Mojoroto Police, Kediri, totaling 57 respondents. The sampling method in this study used non-probability sampling and the sampling technique used purposive sampling, so that the sample in this study was 57 respondents. The regression method used in this study is multiple linear regression analysis. The results showed that the Quality of Work Life, Organizational Commitment and Job Satisfaction on Employee Performance had a positive effect on the Mojoroto Kediri Police. This means that 54% of employee performance can be explained by independent variables, namely Quality of Work Life, Job Satisfaction and Organizational Commitment.